Implications of Tax Reforms in Indirect Tax Collections of the Government of India during the Last Two Decades (2000-2020) - Sanjib Ghimire (International Journal of Engineering and Management Research, 2020)
In this paper, an attempt has been made to analyse the implications of tax reforms after the economic liberalization in 1991 with respect to collection of indirect tax revenue of the Government of India during the last two decades (2000-20). The composition of indirect tax revenue of the Government has undergone a drastic change during the last two decades. Post implementation of the GST Act, the levy of Central Excise has been restricted to petroleum and tobacco products and GST has evolved as the major contributor to the indirect tax revenue collections followed by the Customs Duty. Comparative analysis of indirect tax collections of the Central Government with respect to its growth, share in gross tax revenue, percentage of GDP and composition has been done for the period from 2000-01 to 2019-20. The current study has revealed the growth rate of indirect taxes has not only been uneven but also declined during the year 2001-02, 2008-09 and 2009-10. The share of indirect tax in the gross tax revenue has also gradually declined from 63% in 2000-01 to 46% in 2019-20%. The indirect tax-GDP ratio has remained stagnant in the range of 3.5 to 5.5 % during the last two decades.